Emergency Hospital Care for Exacerbation of COPD: Is Inhaled Maintenance Therapy Modified?. (2nd January 2016) - Pomares, Xavier; Montón, Concepción; Baré, Marisa; Pont, Marina; Estirado, Cristina; Gea, Joaquim; Quintana, José Maria; Vidal, Silvia; Santiago, Ana; ,
Abstract : Background : The impact of hospital emergency care and inward admission for acute exacerbations of COPD on inhaled maintenance treatment is not well known. Objective : Therefore, we evaluated the impact of short-stay emergency hospital care and inward admission for acute exacerbation of COPD (eCOPD) on inhaled maintenance treatment prescribed at discharge. Design : Prospective observational cohort study of patients presenting with eCOPD at emergency departments in 16 hospitals of the Spanish healthcare system. The ethics committee at each hospital approved the study and patients provided an informed consent before inclusion. We classified the patients according to the severity of COPD: mild/moderate (FEV1 ≥ 50% predicted) or severe/very severe (FEV1 < 50% predicted) and need of inward hospitalisation. We analysed changes to maintenance treatment on discharge according to GOLD strategy. Results : 1559 patients, 65% required hospitalisation. The most common maintenance treatment was inhaled corticoids (ICS) (80.9%) followed by long-acting beta-agonists (LABA) (75.4%). The most common combination was triple therapy (LABA+ LAMA+ICS) (56.2%) followed by LABA+ICS dual therapy (18.2%) regardless of the severity of COPD. In more than 60% of patients treatment was not changed at discharge. The most common change in treatment was a reduction when discharge was from emergency care and an increase after hospitalisation (-21.6% and +19.5% in severe/very severe COPD, respectively). Conclusions : Emergency hospital care for eCOPD does not usually induce changes in inhaled maintenance treatment for COPD regardless of the duration of the hospital stay.